Queer Theory and Animal Law - Connor Barnes (Journal of Animal Rights Law, 2025)
Traditional animal law focuses on animals that display humanist traits of value such as autonomy and self-awareness. Therefore, animals worthy of legal recognition under the gaze of traditional animal law must escape their own animality in order to qualify for the law’s protection. In other words, for a whale, dolphin, ape, or elephant (the usual priorities of traditional animal law) to live, the animal within them must die. Queer theory, in particular the concept of ‘utopia’ offered by Jose Esteban Muñoz, ‘Wildness’ by Jack Halberstam, and Michel Foucault’s invention of the ‘homosexual,’ suggests a different way to perceive the animal law field, disengaged from the logic and demands of humanism. Acknowledging the faults of traditional animal law while recognizing the captivity of the term ‘animal’ in an animal/human binary, the application of queer theory concerning animal begets the ‘not-animal,’ a negation of identity that resists ideological capture. The brief examination of the relationship between animality and sexuality that follows aims to illuminate the circular logic of traditional animal law and justify a new terminology and theorization of the many beings who share this planet.